ChemInform Abstract: A Facile Synthesis of Mesoporous Titania Cubes and Their Photocatalytic Application. Issue 19 (21st April 2016) - Chowdhury, Ipsita Hazra; Bose, Pallab; Naskar, Milan Kanti
Abstract: Cube shaped TiO2 is hydrothermally synthesized from aqueous mixtures of TiOSO4, glucose, and EtOH (autoclave, 180 °C, 24 h) followed by calcination at 600 °C for 2 h.